1998
DOI: 10.1136/hrt.79.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Primary antiphospholipid syndrome with acute myocardial infarction recanalised by PTCA

Abstract: A 20 year old man with severe chest pain was hospitalised for acute myocardial infarction. Coronary angiography revealed total obstruction of his right coronary artery, which was successfully recanalised by direct percutaneous transluminal coronary angioplasty (PTCA). There was also diVuse thrombi in the left coronary artery that was not recanalised by perfusion with 3000 U pro-urokinase. Anticoagulant therapy was performed after PTCA. Creatine kinase peaked one day after hospitalisation (4805 U/l). The activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 12 publications
1
17
0
2
Order By: Relevance
“…52 In those patients with myocardial infarction secondary to accelerated premature atherosclerosis, early intervention with primary angioplasty has an improved outcome over thrombolysis. 53 PTCA and stenting should be considered in spontaneous coronary artery dissection and myocardial bridging.…”
Section: Angioplastymentioning
confidence: 99%
“…52 In those patients with myocardial infarction secondary to accelerated premature atherosclerosis, early intervention with primary angioplasty has an improved outcome over thrombolysis. 53 PTCA and stenting should be considered in spontaneous coronary artery dissection and myocardial bridging.…”
Section: Angioplastymentioning
confidence: 99%
“…1 Recent evidence suggests that APS may also result in early atherosclerosis. 2 Several studies have suggested that antiphospholipid antibodies (aPL) may be associated with accelerated atherosclerosis in patients with APS. 3 4 The ankle-brachial index (ABI) is a simple, inexpensive, and non-invasive diagnostic test for lower extremity peripheral arterial disease.…”
mentioning
confidence: 99%
“…However, coronary embolism due to this syndrome is not common [11]. Thus antiphospholipid syndrome may cause acute myocardial infarction due to thrombotic occlusion of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%